Three-Dimensional Digital Documentation for the Conservation of the Prambanan Temple Cluster Using Guided Multi-Sensor Techniques - Anindya Sricandra Prasidya; Irwan Gumilar; Irwan Meilano; Ikaputra Ikaputra; Rochmad Muryamto; Erlyna Nour Arrofiqoh (Heritage)
The Prambanan Temple cluster is a world heritage site that has significant value for humanity, a multiple zone cluster arrangement of highly ornamented towering temples, and a Hindu architectural pattern design. It lies near the Opak Fault, at the foothills of Mount Merapi, on an unstable ground layer, and is surrounded by human activities in Yogyakarta, Indonesia. The site’s vulnerability implies the necessity of 3D digital documentation for its conservation, but its complexity poses difficulties. This work aimed to address this challenge by introducing the utilization of architectural pattern design (APD) to guide multi-sensor line-ups for documentation. First, APDs were established from the literature to derive the associated multiple detail levels; then, multiple sensors and modes of light detection and ranging (Lidar) scanners and photogrammetry were utilized according to their detail requirements and, finally, point cloud data were processed, integrated, assessed, and validated by the proof of the existence of an APD. The internal and external qualities of each sensor result showed the millimeter- to centimeter-range root mean squared error, with the terrestrial laser scanner (TLS) having the best accuracy, followed by aerial close-range and terrestrial-mode photogrammetry and nadiral Lidar and photogrammetry. Two relative cloud distance analyses of every point cloud model to the reference model (TLS) returned the millimeter and centimeter ranges of the mean distance values. Furthermore, visually, every point cloud model from each sensor successfully complemented each other. Therefore, we can conclude that our approach is promising for complex heritage documentation. These results provide a solid foundation for future analyses, particularly in assessing structural vulnerabilities and informing conservation strategies.